(untitled) (REMUNOM, 2023)
Since ancient times, dogs and cats in particular have been a part of human life. This relationship has always been encouraged over time, an association that was initially more related to survival, and in modern times it extends to other benefits, including in the area of health, more specifically to research, in Geriatric Physiotherapy associated with animal-assisted therapy. Objective: It was sought to explain the benefits of Animal Assisted Therapy (TAA) in particular, dogs and cats, in the treatment of older people. For this, a systematic investigation was carried out, through a bibliographic review using databases such as SCIELO (Scientific Electronic Library Online), PEDro (Physiotherapy Evydence Database), BVS (Virtual Health Library), as well as books and scientific articles on geriatric physiotherapy and animal-assisted therapy. In the end, it was considered that it was possible to understand that animal-assisted therapy is effective for physical and emotional well-being, and can be used as a complementary resource in the treatment of a patient. The evidences express the idea of how important it is to use this method as a strategic approach in physiotherapy, since with it it is possible to encourage patients in the rehabilitation process.